2008
DOI: 10.1097/mpa.0b013e318172b4dd
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Celecoxib and the Novel Anti-Cancer Agent, Dimethylamino-Parthenolide, in a Developmental Model of Pancreatic Cancer

Abstract: Dimethylamino-parthenolide and celecoxib have the potential to be novel chemotherapeutic agents for pancreatic cancer; however, further optimization or the use of other modalities may be required for chemoprevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…21 In a hamster carcinogen-induced developmental model of pancreatic cancer, DMAPT alone significantly decreases the size of gross pancreatic cancers relative to placebo; the combination of DMAPT/ celecoxib prevents both tumor invasion and metastasis. 20 Despite demonstrating potential chemotherapeutic efficacy, DMAPT and celecoxib, alone or in combination, do not exhibit chemopreventive activity in this carcinogen-induced model. We have also shown that gemcitabine treatment activates NF-JB in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…21 In a hamster carcinogen-induced developmental model of pancreatic cancer, DMAPT alone significantly decreases the size of gross pancreatic cancers relative to placebo; the combination of DMAPT/ celecoxib prevents both tumor invasion and metastasis. 20 Despite demonstrating potential chemotherapeutic efficacy, DMAPT and celecoxib, alone or in combination, do not exhibit chemopreventive activity in this carcinogen-induced model. We have also shown that gemcitabine treatment activates NF-JB in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 84%
“…19 In xenograft and carcinogen-induced animal models of pancreatic cancer, we demonstrated that DMAPT inhibits the activity of NF-JB and shows therapeutic promise in combination with the anti-inflammatory agents sulindac (nonselective COX inhibitor) or celecoxib (specific COX-2 inhibitor) in vivo. 20,21 We and others have also reported that the chemotherapeutic agent gemcitabine induces NF-JB activity in pancreatic cancer cells in vitro, suggesting that NF-JB may play a role in chemoresistance to gemcitabine. 9,22Y25 We recently demonstrated that DMAPT not only suppresses gemcitabine-induced NF-JB activation but also sensitizes pancreatic cancer cells to the antiproliferative effects of gemcitabine in vitro, indicating that the level of NF-JB activity modulates the gemcitabine response (in press).…”
mentioning
confidence: 91%
“…The reduction in the number of animals with adenomacarcinoma with celecoxib in monotherapy is high compared with previous studies. Schneider et al [49] observed that the administration of celecoxib in monotherapy increases tumor incidence, but with reduced size and invasion capacity, in BOP-treated animals. In this study, the induction period lasted for 6 weeks, and the therapy lasted until 32 weeks after the BOP administration.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with cancer have low levels of antioxidants in tissues, and the induction of oxidative stress by chemotherapy may therefore exacerbate the peripheral cytotoxicity induced by the drug [53]. Different antioxidant agents have also been studied for their antineoplastic activity in monotherapy and in combined administration with other drugs [21,37,49]. It is therefore worth addressing the potential beneficial properties of antioxidants in terms of quality of life and in improving the tolerance to treatment of patients subjected to chemotherapy for pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It has also recently been reported that PTL may inhibit proliferation and apoptosis, and enhance the action of anticancer drugs in various human cancer cells in vitro, including CRC, hepatoma, cholangiocarcinoma, breast cancer, or pancreatic cancer cells. [14][15][16][17][18] However, detailed molecular mechanisms of these anticancer effects of PTL are largely unknown. The water-soluble Michael adduct of PTL, dimethylaminoparthenolide (DMAPT), shows improved solubility and bioavailability compared with PTL and has entered clinical trials for cancer therapy.…”
mentioning
confidence: 99%